499 OUTCOMES AND POTENTIAL ADVERSE EVENTS FOR CHRONIC PAIN PATIENTS IN A MUSCULOSKELETAL SPINE CLINIC ON INTERVENTIONAL CYCLOOXYGENASE 2 INHIBITORS. (1st January 2006) - Mehta, N.; Gurbani, A.; Fish, D. E.
Abstract : Background: Up until recently, cyclooxygenase (COX)-2 selective agents were thought to have a significant advantage over conventional NSAIDs in terms of toxic effects, notably GI complications. For degenerative arthritis and various types of spine pain, COX-2 inhibitors had been frequently used as first-line therapy in the absence of any overt inflammation. This raises issues about both the appropriateness of prescribing coxibs and the rate of adverse events in low-dose short-term use in outpatient musculoskeletal clinics. Because pain relief in a multidisciplinary spine clinic can be challenging and had often been treated with many of the now off-market COX-2 selective agents, more data need to be gathered for the outcomes of those patients on low-dose therapy for pain relief. Objective: To determine the rate of adverse events for COX-2 selective agents when used in low doses for patients with various types of musculoskeletal pain. Hypothesis: We expect that patients will tolerate medications with minimal adverse events. Methods/Design: Of the 431 musculoskeletal spine pain patients in an outpatient clinic that were prescribed COX-2 selective agents, 220 were contacted and 55 successfully completed a self-assessment questionnaire. Main Outcome Measure: Pain relief and presence of adverse events: rash, CP/SOB, GI disturbances, etc. Results: 67% reported significant pain relief; 23.6% reported an adverse event during the period coinciding with COX-2 inhibitor use (Celebrex, Vioxx, Bextra, Mobic). Self-reported PMH: 25% hyperlipidemia, 47% hypertension (HTN), 18% heart disease, 18% GI disturbances, 11% gastric ulcers. Overall, 9% cited potential side effects as reason for discontinuing NSAID use. Of the 33% of patients reporting blood thinner use, 61% reported significant pain relief; 28% reported adverse events. Conclusion: In the small population ( N = 55) evaluated, the pilot study finds minimum adverse events for all COX-2 selective agents when compared to reported literature rates of 31% (2000 CLASS study). Those with risk factors for potential adverse events did not report more events than those without risk factors while on COX-2 selective agents. The pilot study suggests that patients on low-dose COX-2 selective agents obtain pain relief with a low occurrence of adverse events and an even lower occurrence of serious adverse outcomes. More patient evaluations will be necessary to confirm the trends found in this pilot study.